AFTER GOD, AFTER ISLAM - Saputro, Muhammad Endy (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2011)
Tulisan ini bertujuan mendiskusikan agama di era postmodern, dengan fokus pertanyaan bagaimana menjadi muslim dan memahami Qurâan di era post-modern. Memakai pemikiran Don Cupitt, dalam beberapa karyanya, tulisan ini berargumen bahwa mengandaikan Tuhan telah mati merupakan jalan alternatif memahami Qurâan agar lebih kontekstual diaplikasikan dalam kehidupan masyarakat muslim di era postmodern. Signifikansi utama tulisan ini adalah memberikan kontribusi alternatif dalam dimensi filosofis kerangka berpikir kontekstualisasi Qurâan. Â —————This article aimed to examine the Cupittâs conception in the light of Islamic paradigm. It is done by identifying negative impacts of postmodernism toward the existence of religion. Religion, in Don Cuppit view is alive in the term of âvalueâ, âprivate realmâ, âpersonal faithâ and âcountercultureâ. Although Islam came from hundreds centuries ago, it does not mean that authentic Islam is Islam in the past. Islam in the past, Islam in the present and Islam in the future are different. Islam is not timeless doctrine, but changeable expression. Time is running; and Islam demanded to contextualize itself dynamically.